2011
DOI: 10.1152/ajpheart.00383.2011
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of diabetic vasculopathy in a rat model of type 1 diabetes by opiorphin-related peptides

Abstract: Diabetes results in a myriad of vascular complications, often referred to as diabetic vasculopathy, which encompasses both microvascular [erectile dysfunction (ED), retinopathy, neuropathy, and nephropathy] and macrovascular complications (hypertension, coronary heart disease, and myocardial infarction). In diabetic animals and patients with ED, there is decreased opiorphin or opiorphin-related gene expression in corporal tissue. Both opiorphin and the rat homologous peptide sialorphin are found circulating in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Indeed, there is some evidence that ketoconazole and prednisone, which reduce circulating testosterone levels, can help prevent recurrent ischemic priapism (51), and, potentially, some of their physiological activity could be mediated through decreased opiorphin expression. In addition, as described above, opiorphin can be detected in the bloodstream and saliva of patients (52), and in rats, levels of vcsa1 expression in corporal tissue are reflected by sialorphin levels in the blood (47). Therefore, opiorphin levels in the blood are potentially a useful biomarker for SCD‐related priapic crisis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, there is some evidence that ketoconazole and prednisone, which reduce circulating testosterone levels, can help prevent recurrent ischemic priapism (51), and, potentially, some of their physiological activity could be mediated through decreased opiorphin expression. In addition, as described above, opiorphin can be detected in the bloodstream and saliva of patients (52), and in rats, levels of vcsa1 expression in corporal tissue are reflected by sialorphin levels in the blood (47). Therefore, opiorphin levels in the blood are potentially a useful biomarker for SCD‐related priapic crisis.…”
Section: Discussionmentioning
confidence: 97%
“…The mechanism described here, where hypoxic upregulation of sialorphin results in transcriptional activation of Hif‐1a and A2BR, may be restricted to CSM tissue, which under normal physiological conditions expresses high levels of vcsa1 relative to other tissues (15‐18). However, we have previously demonstrated that changes in expression of vcsa1 in rat corporal tissue are reflected by circulating levels of sialorphin in the blood (47). We have demonstrated that gene transfer of vectors into rat corporal tissue can increase sialorphin levels in the blood of diabetic rats, and the increased levels of sialorphin in blood are associated with reduced systemic blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…erectile function [59,[61][62][63][64], through relaxation of corporal smooth muscle tissue through a GPCR (G-protein coupled receptor) mechanism [62,65].…”
Section: Submandibular Gland Peptide T (Sgp-t)mentioning
confidence: 99%
“…This workflow is associated with procedural risks, reduction of patient quality of life, exposure to ionizing radiation, and high costs . Few studies have specifically addressed CMD treatment, despite the fact that several drugs proved effective in restoring microvascular function in animal models of MD . This in part reflects the absence of a single tool for the diagnosis of CMD and to monitor effects of therapy.…”
Section: Functional Assessment Of the Coronary Microcirculationmentioning
confidence: 99%